Aspects of cooperation of school and home in the light of the official journals of education departments of school districts in Poland in the years 1932–1939 - Magiera, Elżbieta (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
In this article I have made an analysis of the official journals of the individual school district departments of education in the years 1932–1939 in the context of thecooperation between the school and the families of the students. On the pages of the analyzed magazines the issues associated with the cooperation of school with the family of the student were raised. Its causes were searched for, it was attempted to justify it with the broad socio-cultural determinants, changes of family and school as an institution of teaching and education.
Keywords: history of education; interwar period; cooperation of school and home; Second Republic; parents; school districts; education departments; official journals